What's happening to our news - Currah, A (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford (RISJ), 2009)
This book looks at how the quality and commercial viability of British journalism are under critical threat from the digital revolution. Advertisers are deserting newspapers and television news programmes for the web, draining resources away from newsgathering. Threatening to ‘hollow out’ the craft of journalism, this process has potentially serious civic consequences. News companies have turned to the internet to expand their reach and profit from digital advertising. Many are developing a strong multimedia presence and providing information in web-friendly bite-size chunks, but advertisers increasingly favour search engines over standalone news sites. The outlook is made worse by the current recession, which is accelerating the migration of advertising from traditional media to the web.